Framing techniques for IP over fiber. - Bonenfant, P.
We provide a high-level but extensive overview of the protocols and framing techniques for mapping IP packets over fiber in metropolitan, regional, and wide area fiber optic networks
Keywords: ATM; DWDM systems; Gigabit Ethernet; IP over fiber; IP packets mapping; IP routers; MAN; SONET/SDH.; WAN; Dense wavelength-division multiplexing; Framing techniques; Metropolitan area fiber optic networks; Protocols; Regional area fiber optic networks; Wide area fiber optic networks